An analytical approach to the ventilation effectiveness of mediterranean buildings: case study: existing residential building, Portugal - Salehi, Atefeh (2016)
Building airtightness assumes an important role in the energy saving and the indoor thermal comfort. Ventilation rates bring significant impacts on energy usage in the constructions and indoor contaminant concentrations and also setting them as the key parameters in building performance. Ventilation rate have been measured in building for a long time, and there are some developed measurement methodologies related to it in the research domains. However, most of the investigations in recent years have been done usually in the cold climate conditions, while Mediterranean construction are not deeply investigated in the literature. In this paper, the authors present the obtained results of an experimental research which is carried out on the Portuguese residential buildings. The investigation is done by fan pressurization methods, also known as “Blower Door Test (BDT)” as the measurement method as well as Design Builder (DB) as the simulation software. The airtightness measurement of the existing buildings and the influence of air leakage on energy consumption and indoor comfort in different Portuguese construction typologies are focused on the aim of the research. The important parameters of the building such as whole-building air change rates, building infiltration rates, and ventilation effectiveness rate in the residential building are also considered in this research.